The recreational space preference of the students in Iloilo City based on some social demographic variables - Cameña, Keith D.
The study attempted to find a relationship across varying socio-demographics characteristics of students of Iloilo City ( sex, age, university enrolled in, number of units being take, degree program enrolled in, employment status and weekly allowance and/or budget) and their recreational space to be built in the proposed site in Nabitasan, la Paz, Iloilo CityThe study was conducted in the two major universities in Iloilo City located more or less within one kilometer radius of the site, namely the University of San Agustin and University of the Philippines-Iloilo. Forty respondents from each university answered the pre-tested questionnaire. Results of the chi-square reveal that there is nosignificant relationship between any of the socio-demographic characteristics of the students and their recreational space preference. One probable intervening variable could be the prior experience of the experienced respondents or the perceived novelty of the experience of the inexperienced ones. Based on the results, the researchers recommend that other sociodemographic characteristics be included, or other respondents from different socio-demographic categories be considered. It is also recommended that future developers or policy-makers consider the social needs of their stakeholders rather than cater only to the market demands in recreation. Policy-makers and the city government must also look intourban enhancement when planning for the recreational needs of their stakeholders so that not only the leisure needs are taken care of but also the quality of life of the urban population as a whole.